2011
DOI: 10.1093/hmg/ddr033
|View full text |Cite
|
Sign up to set email alerts
|

APP-dependent up-regulation of Ptch1 underlies proliferation impairment of neural precursors in Down syndrome

Abstract: Mental retardation in Down syndrome (DS) appears to be related to severe neurogenesis impairment during critical phases of brain development. Recent lines of evidence in the cerebellum of a mouse model for DS (the Ts65Dn mouse) have shown a defective responsiveness to Sonic Hedgehog (Shh), a potent mitogen that controls cell division during brain development, suggesting involvement of the Shh pathway in the neurogenesis defects of DS. Based on these premises, we sought to identify the molecular mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
118
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 63 publications
12
118
1
1
Order By: Relevance
“…A combination of environmental enrichment and enhanced physical exercise starting in young mice resulted in a strongly increased neurogenesis rate in the dentate gyrus comparable to that of euploid mice. 42 In addition to an increased gene dose of full-length APP, levels of fragments derived from proteolytical APP processing are also elevated in Ts65Dn mice 43 and likely also in mouse models with APP overexpression. A normalization of the triplicated APP expression using APP shRNA lentiviral particles led to a restoration of neuronal maturation and differentiation and increased neuriteoutgrowth to normal levels in a dose-dependent manner.…”
Section: App Expression and Its Impact On Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of environmental enrichment and enhanced physical exercise starting in young mice resulted in a strongly increased neurogenesis rate in the dentate gyrus comparable to that of euploid mice. 42 In addition to an increased gene dose of full-length APP, levels of fragments derived from proteolytical APP processing are also elevated in Ts65Dn mice 43 and likely also in mouse models with APP overexpression. A normalization of the triplicated APP expression using APP shRNA lentiviral particles led to a restoration of neuronal maturation and differentiation and increased neuriteoutgrowth to normal levels in a dose-dependent manner.…”
Section: App Expression and Its Impact On Neurogenesismentioning
confidence: 99%
“…Trisomic neural precursor cells derived from Ts65Dn mice have been demonstrated to exhibit increased expression levels of the Shh receptor Ptch1, resulting in suppression of Smoothend (Smo), a second receptor involved in this signaling pathway. 43 Elevated AICD levels, and therefore increased AICD binding to the Ptch1 promotor, resulted in Ptch1 overexpression while Ptch1 silencing using antisense oligonucleotides lead to a restoration of cell proliferation in trisomic neural precursor cells. 43 In support of this observation, a recent study has been demonstrated that g-secretase inhibitor treatment normalized AICD levels and restored impaired neurogenesis and Sonic Hedgehog signaling in Ts65Dn-derived neurospheres.…”
Section: Role Of the Aicd Fragment In Altered Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Neural precursor cells from the subventricular zone (SVZ) of Ts65Dn mice exhibit a higher expression of the sonic hedgehog (Shh) receptor patched1 (Ptch1). 13 Ptch1 exerts a negative effect on the membrane receptor smoothened (Smo). Smo is responsible for activating the downstream element of the Shh pathway, thereby stimulating cell proliferation.…”
mentioning
confidence: 99%
“…Our group has previously shown that the increased expression of Ptch1 in neural precursors of trisomic mice is due to an excessive formation of amyloid precursor protein intracellular domain, a soluble fragment of amyloid precursor protein (APP). 13 As APP is a trisomic gene, its over expression may also cause an increased expression of Ptch1 in peripheral tissues, which, in turn, may reduce proliferation potency.…”
mentioning
confidence: 99%